2015
DOI: 10.1111/jfq.12151
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Bread and Cookie Baked from Frozen Dough and Batter Containing β‐Glucan‐Rich Barley Flour Fraction

Abstract: Prolonged frozen storage of dough and batter unfavorably affects the quality of end baked products. The effect of air-classified barley flour fraction rich in β-glucan (∼25%) on the quality of bread and cookie baked from frozen dough/ batter was investigated. Dough and batter were stored at −18C for 8 and 4 weeks, respectively, and evaluated for baking quality at weekly intervals. Bread made from fresh control dough produced the highest loaf specific volume (LSV) compared with those baked from composite dough.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
4
4
1
Order By: Relevance
“…Dietary fibre is an important ingredient for a new generation of healthier food products that satisfy consumer demands and is highly recommended as an additive to white wheat cereal products such as white bread (Borczak et al 2012; Martínez‐Monzó et al 2013). In contrast to the positive health effects, however, our study, as well as others, found that fibre‐supplemented bread shows a pronounced decrease in sensory quality over time compared with white bread (Hamed et al 2015; Gómez & Martinez 2018). The addition of fibre to bakery products significantly modifies the properties of the dough and the final product (Katina et al 2006; Noort et al 2010; Curti et al 2013) and alters the production process (Collar et al 2007).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Dietary fibre is an important ingredient for a new generation of healthier food products that satisfy consumer demands and is highly recommended as an additive to white wheat cereal products such as white bread (Borczak et al 2012; Martínez‐Monzó et al 2013). In contrast to the positive health effects, however, our study, as well as others, found that fibre‐supplemented bread shows a pronounced decrease in sensory quality over time compared with white bread (Hamed et al 2015; Gómez & Martinez 2018). The addition of fibre to bakery products significantly modifies the properties of the dough and the final product (Katina et al 2006; Noort et al 2010; Curti et al 2013) and alters the production process (Collar et al 2007).…”
Section: Discussioncontrasting
confidence: 87%
“…However, the addition of fibre can also negatively affect the final quality of bread. It is associated with changes in texture, like firmness and springiness; colour darkening; and change of taste (Gómez et al 2011; Hamed et al 2015). The most obvious effect is a reduction in loaf volume due to the disruption of the starch‐gluten matrix (Collar et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…All the powders have a water activity below 0.60 that prevents microbiological proliferation or degradation of phenolic compounds (Hamed and others ). The inlet drying temperature had a significant effect on water activity ( a w ) and particularly the powders obtained at 200 °C had similar or lower a w than the reported for nixtamalized corn flours (Milán‐Carrillo and others ).…”
Section: Resultsmentioning
confidence: 99%
“…To measure sweet bread expansion volume, the loaves were weighed using analytical balance and the volume was recorded using rapeseed displacement method (official AACE International method 10-05-01). Furthermore, the specific volume was calculated by dividing the volume-expanded bread weight with sweet bread weight (cm 3 g -1 ) (Hamed et al, 2015). iv.…”
Section: Observed Parametersmentioning
confidence: 99%